The Mediation of Education and Tenure on the Perpormance of Employees - Dewa Putu Yohanes Agata L. Sandopart; Budiman Abdulah; Annisa Pratiwi Ramdini; Erma Wijayanti; Dewa Ayu Indiana Ida L. Sandopart (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
Factors influencing employee performance are a big concern for businesses in an increasingly dynamic workplace. Tenure and educational attainment are key factors in raising labor productivity. While tenure-based experience enables employees to develop competence, adaptability, and effectiveness in completing their tasks, education provides the fundamental knowledge and skills required for the job (Noe, 2020). However, without sufficient work experience, education alone is insufficient. Tenure permits individuals to comprehend company culture, strengthen technical and interpersonal abilities, and improve efficiency in completing their jobs (Robbins & Judge, 2019). Therefore, when developing human resource management strategies, businesses must have a thorough understanding of how these two factors affect employee performance. This research aims to determine the significant influence between education level and length of service on employee performance partially and simultaneously for employees of the Grand Sahid Jaya Hotel Jakarta. This research design is causal using primary data obtained from the results of the questionnaire. The population in this research was all 50 employees. The data analysis technique used in this research uses a questionnaire method, for data processing using statistical software SPSS Version 28. The research results show that education level and length of service influence employee performance partially and simultaneously.